PENGARUH PEMBERIAN KOMPOSISI PAKAN TEPUNG TONGKOL JAGUNG YANG BERBEDA TERHADAP PERTUMBUHAN IKAN TAWES (Puntius javanicus) - Aan Novrianto; Yulfiperius Yulfiperius; Andriyeni Andriyeni; Asro Nurhabib; Supriyono Supriyono (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2019)
This research was conducted in April s / d June 2017 located in Fisheries Laboratory of University Prof. Dr. Hazairin, SH Bengkulu. The design of this study used a Completely Randomized Design with 4 Treatments and 6 repeats. The treatments were (1) = CornCob 157 gram, (2) = Corncob 167 gram, (3) = CornCob 177 gram, (4) = Corncob 187 gram. To know the effect or not done an analysis of variance and continued with a test of the Duncan Multiple Range Test (DMRT) 5% and 1%. The parameters observed were absolute weight, absolute length, feed conversion, feed efficiency, and fish survival. The results showed that giving different feed composition of corn cob feed was a significant effect on absolute weight growth, absolute length, feed conversion, feed efficiency but no significant effect on survival of Tawes (Puntius javanicus). Absolute weight growth, absolute length, feed conversion, and feed efficiency are best found in Treatment P1 = Corncob 157 grams and survival of Tawes (Puntius javanicus) 100%.